Adhesive composition

By using an adhesive composition of an amino group-containing styrene-based elastomer and an epoxy resin, the problem of insufficient adhesion and operability of existing low-dielectric adhesives in high-frequency electronic parts is solved, and the problem of insufficient adhesion and operability of existing low-dielectric adhesives in high-frequency electronic parts is realized. High adhesiveness and excellent electrical properties for lower temperature curing.

CN114867807BActive Publication Date: 2025-01-03SHIN ETSU POLYMER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080090044.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-23
Filing Date
2020-10-19
Publication Date
2025-01-03
Estimated Expiration
2040-10-19

AI Technical Summary

Technical Problem

The adhesion of existing low-dielectric adhesives has not yet reached an ideal level after heating and curing, and the limitations of curing temperature and time lead to poor operability, making it difficult to meet the needs of high-frequency electronic parts for adhesion and electrical characteristics.

Method used

Using an adhesive composition of a styrene-based elastomer containing amino groups and an epoxy resin, the total nitrogen amount of the amino group and the content of the epoxy resin are adjusted to reduce the softening point of the epoxy resin to achieve lower temperature curing, while optimizing Epoxy compounds of styrene-butadiene block copolymers to improve the heat resistance and chemical resistance of the adhesive.

Benefits of technology

It achieves high adhesion and excellent adhesion at lower temperatures, while improving the operability and electrical characteristics of the adhesive, which is suitable for the bonding needs of high-frequency electronic parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003710311080000071
    Figure BDA0003710311080000071
  • Figure BDA0003710311080000251
    Figure BDA0003710311080000251
Patent Text Reader

Abstract

The present invention provides an adhesive composition having excellent electrical properties and capable of forming an adhesive layer having excellent adhesion (adhesion) after heat curing, wherein the adhesive layer has excellent adhesion (adhesion) even when cured at a lower temperature, and can improve workability. The adhesive composition comprises a styrene elastomer containing an amino group and an epoxy resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition and, more particularly, to an adhesive composition that can be used for bonding electronic components and the like. Background Art

[0002] As electronic devices become smaller and lighter, the applications of bonding electronic parts and the like are diversified, and the demand for laminates with adhesive layers is increasing.

[0003] In addition, in a flexible printed circuit board (hereinafter also referred to as FPC), which is a kind of electronic component, a large amount of data needs to be processed at high speed, and the response to high frequencies is progressing. In order to achieve high frequencies in FPC, the dielectric properties of the components need to be lowered, and the development of low-dielectric substrate films and low-dielectric adhesives is underway.

[0004] However, since low-dielectric adhesives have low molecular polarity, it is difficult to demonstrate adhesion (bonding) with substrate films and other components related to electronic parts. In addition, low-dielectric substrate films also sometimes have poor adhesion (bonding) with adhesives, and the adhesion needs to be improved.

[0005] Therefore, in order to have good electrical properties (low relative dielectric constant and low dielectric loss tangent) and cope with high adhesion, it is proposed to use an adhesive composition containing a carboxyl-containing styrene elastomer (A) and an epoxy resin (B), and to form a laminate comprising an adhesive layer composed of the adhesive composition and a substrate film (for example, refer to Patent Document 1).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2016 / 017473 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, although the adhesive composition described in Patent Document 1 exhibits a certain degree of high adhesion (tackiness) after being cured by heat, there is still room for improvement in terms of improving the adhesion (tackiness).

[0011] In addition, the low dielectric adhesive has less reactive substituents with high polarity in order to reduce relative dielectric constant. Therefore, when curing temperature can not be reduced or curing time is long, operability is poor, and there is limitation in the device that can be used. From the viewpoint of practicality, even if it is desired to provide curing with lower temperature, high adhesion (adhesiveness) can be embodied, and the adhesive that can improve operability can be improved.

[0012] Therefore, an object of the present invention is to provide an adhesive composition having excellent electrical properties and capable of forming an adhesive layer having excellent adhesion (tackiness) after heat curing, wherein the adhesive layer has excellent adhesion (tackiness) even when cured at a further lower temperature, and can improve workability.

[0013] Technical solutions to solve problems

[0014] The present inventors have repeatedly conducted in-depth studies to solve the above-mentioned problems. As a result, they have found that an adhesive composition comprising an amino group-containing styrene elastomer and an epoxy resin not only exhibits high adhesion (adhesion) to a substrate film after heat curing, but also exhibits excellent adhesion (adhesion) even when cured at a lower temperature. The present inventors have excellent operability, and are able to solve the above-mentioned problems, thereby completing the present invention.

[0015] The present invention includes the following aspects.

[0016] [1] An adhesive composition comprising a styrene-based elastomer containing an amino group and an epoxy resin.

[0017] [2] The adhesive composition according to [1], wherein the content of the epoxy resin is 1 to 20 parts by mass based on 100 parts by mass of the adhesive composition.

[0018] [3] The adhesive composition according to [1] or [2], wherein the total nitrogen content of the amino group-containing styrene elastomer is 50 to 5000 ppm.

[0019] [4] The adhesive composition according to any one of [1] to [3], wherein the epoxy resin has a softening point or a melting point of 90° C. or less.

[0020] [5] An adhesive composition according to any one of [1] to [4], wherein the epoxy resin is a novolac type epoxy resin.

[0021] [6] The adhesive composition according to any one of [1] to [4], wherein the epoxy resin is a glycidylamine-type epoxy resin.

[0022] [7] The adhesive composition according to any one of [1] to [4], wherein the epoxy resin is an epoxy compound of a styrene-butadiene block copolymer.

[0023] [8] An adhesive layer formed by curing the adhesive composition described in any one of [1] to [7], wherein the relative dielectric constant of the adhesive layer measured at a frequency of 28 GHz is 3.5 or less, and the dielectric loss tangent is 0.01 or less.

[0024] [9] A laminated body comprising:

[0025] a substrate film; and

[0026] An adhesive layer comprising the adhesive composition according to any one of [1] to [7], or an adhesive layer according to [8].

[0027]

[10] The laminate according to [9], wherein the base film contains polyetheretherketone (PEEK) resin.

[0028]

[11] A cover film with an adhesive layer, comprising the laminate according to [9] or

[10] .

[0029]

[12] A copper-clad laminate comprising the laminate described in [9] or

[10] .

[0030]

[13] A printed wiring board comprising the laminate according to [9] or

[10] .

[0031]

[14] A shielding film comprising the laminate according to [9] or

[10] .

[0032]

[15] A printed wiring board with a shielding film, comprising the laminate described in [9] or

[10] .

[0033] Effects of the Invention

[0034] According to the present invention, an adhesive composition having excellent electrical properties and capable of forming an adhesive layer having excellent adhesion (tackiness) after heat curing can be provided, wherein the adhesive composition has excellent adhesion (tackiness) even when cured at a further lower temperature and can improve workability. DETAILED DESCRIPTION

[0035] The adhesive composition of the present invention, a laminate containing an adhesive layer containing the adhesive composition, and constituent members related to electronic components containing the laminate are described in detail below, but the description of the constituent elements described below is an example of one embodiment of the present invention and is not limited to these contents.

[0036] (Adhesive composition)

[0037] The adhesive composition of the present invention comprises an amino-containing styrene elastomer and an epoxy resin. The adhesive composition of the present invention may also comprise a styrene elastomer other than the amino-containing styrene elastomer (e.g., a carboxyl-containing styrene elastomer) as required. In addition, the adhesive composition of the present invention may also contain other components as required.

[0038] <Amino group-containing styrene elastomer>

[0039] By including an amino group-containing styrene elastomer in the adhesive composition, the adhesion of the adhesive layer is improved, especially the adhesion to metal is improved. In addition, the amino group-containing styrene elastomer is reactive, so the heat resistance and chemical resistance of the adhesive layer are also improved by epoxy curing.

[0040] By including an amino group-containing styrene-based elastomer in the adhesive composition, excellent adhesion (tackiness) can be exhibited even when the composition is cured at a lower temperature.

[0041] The amino group-containing styrene-based elastomer is a copolymer mainly composed of a block or random structure of a conjugated diene compound and an aromatic vinyl compound, and a hydrogenated product thereof which has been subjected to amine modification.

[0042] Examples of the aromatic vinyl compound include styrene, tert-butylstyrene, α-methylstyrene, divinylbenzene, 1,1-diphenylethylene, N,N-diethyl-p-aminoethylstyrene, vinyltoluene, etc. Examples of the conjugated diene compound include butadiene, isoprene, 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene.

[0043] The method for amine-modifying the styrene-based elastomer is not particularly limited, and a known method can be adopted, for example, a method of amine-modifying a (hydrogenated) block copolymer by polymerizing it using a polymerization initiator having an amino group; a method of amine-modifying a (hydrogenated) copolymer by using an unsaturated monomer having an amino group as a raw material for copolymerization; a method of amine-modifying a (hydrogenated) copolymer by reacting an amine modifier having two or more amino groups with a styrene-based elastomer containing a carboxyl group to form an amide structure or an imide structure, etc.

[0044] In addition, the weight average molecular weight of the amino group-containing styrene elastomer is preferably 10,000 to 500,000, more preferably 300,000 to 300,000, and further preferably 50,000 to 200,000. If the weight average molecular weight is above the above lower limit, excellent adhesion can be achieved, and the coating property when dissolved in a solvent and applied is also good. If the weight average molecular weight is below the above upper limit, the compatibility with the epoxy resin becomes good.

[0045] The weight average molecular weight is a value calculated in terms of polystyrene of the molecular weight measured by gel permeation chromatography (hereinafter, referred to as “GPC”).

[0046] Specific examples of styrene-based elastomers containing amino groups include products obtained by subjecting styrene-butadiene block copolymers, styrene-ethylene propylene block copolymers, styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, styrene-ethylene butylene-styrene block copolymers, and styrene-ethylene propylene-styrene block copolymers to amine modification using compounds having amino groups.

[0047] These amino group-containing styrene-based elastomers may be used alone or in combination of two or more.

[0048] Among the above copolymers, styrene-ethylene butylene-styrene block copolymers and styrene-ethylene propylene-styrene block copolymers are preferred from the viewpoints of adhesiveness and electrical properties.

[0049] In addition, the mass ratio of styrene / ethylene butylene in the styrene-ethylene butylene-styrene block copolymer and the mass ratio of styrene / ethylene propylene in the styrene-ethylene propylene-styrene block copolymer are preferably 10 / 90 to 50 / 50, and more preferably 20 / 80 to 40 / 60. As long as the mass ratio is within this range, an adhesive composition having excellent adhesive properties can be prepared.

[0050] The content of the amino group-containing styrene-based elastomer is preferably 25.0 to 99.0 parts by mass based on 100 parts by mass of the solid content of the adhesive composition. When the content is within this range, an adhesive composition having excellent adhesive properties can be obtained.

[0051] From the viewpoint of ensuring the low relative dielectric constant and adhesion (adhesion) of the adhesive composition, the total nitrogen content in the amino-containing styrene elastomer is preferably 50 to 5000 ppm, more preferably 200 to 3000 ppm. If the total nitrogen content is above the above lower limit, excellent adhesion can be achieved. If the total nitrogen content is below the above upper limit, excellent electrical properties are achieved.

[0052] The total nitrogen content in the amino group-containing styrene-based elastomer can be determined, for example, using a trace nitrogen analyzer ND-100 Model (manufactured by Mitsubishi Chemical Corporation) in accordance with JIS-K2609.

[0053] <Epoxy resin>

[0054] The epoxy resin is a component that reacts with the amino group in the amino group-containing styrene elastomer and exhibits high adhesion to an adherend and heat resistance of the cured adhesive.

[0055] Examples of epoxy resins include: bisphenol A epoxy resin, bisphenol F epoxy resin, or epoxy resins hydrogenated from these; glycidyl ester epoxy resins such as diglycidyl phthalate, diglycidyl isophthalate, diglycidyl terephthalate, glycidyl p-hydroxybenzoate, diglycidyl tetrahydrophthalate, diglycidyl succinate, diglycidyl adipate, diglycidyl sebacate, and triglycidyl trimellitate; ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether , 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, tetraphenyl glycidyl ether ethane, triphenyl glycidyl ether ethane, polyglycidyl ether of sorbitol, polyglycidyl ether of polyglycerol and other glycidyl ether epoxy resins; triglycidyl isocyanurate, tetraglycidyl diaminodiphenylmethane and other glycidyl amine epoxy resins; epoxidized polybutadiene, epoxidized soybean oil and other linear aliphatic epoxy resins, but not limited to these. In addition, novolac epoxy resins containing xylene structure, naphthol novolac epoxy resins, phenol novolac epoxy resins, o-cresol novolac epoxy resins, bisphenol A novolac epoxy resins and other novolac epoxy resins can also be used.

[0056] In addition, as examples of epoxy resins, there can be used brominated bisphenol A type epoxy resins, phosphorus-containing epoxy resins, fluorine-containing epoxy resins, epoxy resins containing dicyclopentadiene skeletons, epoxy resins containing naphthalene skeletons, anthracene-type epoxy resins, tert-butylcatechol-type epoxy resins, triphenylmethane-type epoxy resins, tetraphenylethane-type epoxy resins, biphenyl-type epoxy resins, bisphenol S-type epoxy resins, etc. These epoxy resins may be used alone or in combination of two or more.

[0057] Among the above epoxy resins, epoxy resins without hydroxyl groups are preferred from the viewpoint of obtaining an adhesive composition with excellent electrical properties and good compatibility with styrene-based elastomers. In particular, novolac epoxy resins and epoxy resins having the following structure are epoxy resins having a moderately soft skeleton, and therefore, the cured product is less likely to cause brittle failure, and the long-term use performance stability of the cured product of the adhesive composition is improved, and the number of functional groups is also high, so the heat resistance is also improved, and therefore, they are more preferred.

[0058] [Chemical formula 1]

[0059]

[0060] (R is a structure containing methylene-aryl-methylene, or a structure containing an aliphatic hydrocarbon structure having 6 or more carbon atoms. Examples of the aryl group include benzene, xylene, naphthalene, biphenyl, and the like, and examples of the aliphatic hydrocarbon include hexane, dimethylcyclohexane, dicyclopentadiene, and the like.)

[0061] Specific examples of novolac-type epoxy resins include, for example, "YX7700" manufactured by Mitsubishi Chemical Corporation (xylene structure-containing novolac-type epoxy resin), "NC7000L" manufactured by Nippon Kayaku Co., Ltd. (naphthol novolac-type epoxy resin), "ESN485" manufactured by Nippon Steel Chemical & Material Co., Ltd. (naphthol novolac-type epoxy resin), "N-690" manufactured by DIC Corporation (cresol novolac-type epoxy resin), and "N-695" manufactured by DIC Corporation (cresol novolac-type epoxy resin). More preferably, the epoxy compound is a styrene-butadiene block copolymer. The epoxy compound of styrene-butadiene block copolymer, in the reaction of epoxy structure, in addition to the aromatic ring such as olefin skeleton and vinyl, also involves unsaturated bonds, thus, it is possible to promote reaction speed and improve crosslinking density, and as a result, even if it is a small amount of mixing, it is possible to improve heat resistance and chemical resistance. In addition, the molecular weight of the epoxy compound of styrene-butadiene block copolymer is large, and it contains epoxy groups, thus, it plays a role as a dispersant, and further improves the dispersibility of inorganic fillers. As the epoxy compound of styrene-butadiene block copolymer, commercially available epoxy compounds can also be used, for example, it can be cited: CELLOXIDE 2021P, CELLOXIDE 2081, CELLOXIDE 2000 (DAICEL company system), Epolide GT401, Epolide PB3600, Epolide PB4700 (DAICEL company system), Epofriend AT501, Epofriend CT310 (DAICEL company system).

[0062] In addition, the epoxy resin having an amino group can shorten the curing time or lower the curing temperature by the catalytic action of the amino group, thereby improving workability. In addition, since the epoxy resin contains an amino group, the adhesion with the metal layer is improved.

[0063] In particular, the epoxy resin is preferably a glycidylamine epoxy resin. Glycidylamine epoxy resin is multifunctional and can be cured in a small amount. It contains amines in the molecular skeleton and has good compatibility with amino-containing styrene elastomers and has a reaction-promoting effect. In addition, since it contains an amine group, it can improve the adhesion with the metal layer.

[0064] Specific examples of glycidylamine-type epoxy resins include tetraglycidyldiaminodiphenylmethane, such as "jER604" manufactured by Mitsubishi Chemical Corporation, "SUMI-EPOXYELM434" manufactured by Sumitomo Chemical Co., Ltd., "Araldite MY720", "Araldite MY721", "Araldite MY9512", "Araldite MY9612", "Araldite MY9634", "Araldite MY9663" manufactured by Huntsman Advanced Materials, and "TETRAD-X" and "TETRAD-C" manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0065] As the epoxy resin used in the present invention, an epoxy resin having two or more epoxy groups in one molecule is preferred. This is because a cross-linked structure can be formed in the reaction with the amino-containing styrene elastomer, thereby exhibiting high heat resistance. In addition, when an epoxy resin having two or more epoxy groups is used, the degree of cross-linking with the amino-containing styrene elastomer is sufficient, thereby obtaining sufficient heat resistance.

[0066] The content of the epoxy resin is preferably 1 to 20 parts by mass relative to 100 parts by mass of the solid content of the adhesive composition. If the content of the epoxy resin is above the lower limit, the adhesive composition can be fully cured to ensure good heat resistance and chemical resistance. On the other hand, when the content of the epoxy resin is high, the adhesion is reduced, so if it is below the upper limit, good adhesion can be ensured.

[0067] The softening point or melting point of the epoxy resin is preferably below 90°C. When the softening point or melting point of the epoxy resin is below 90°C, the glass transition point of the adhesive composition can be lowered, the elastic modulus of the adhesive composition before curing in the high temperature region can be lowered, and the elastic modulus of the adhesive composition after curing in the normal temperature region (room temperature) can be increased. In addition, the epoxy resin is preferably dissolved at the reaction temperature because the reaction is fast.

[0068] <Carboxyl group-containing styrene elastomer>

[0069] As described above, the adhesive composition of the present invention may contain a styrene-based elastomer other than the amino group-containing styrene-based elastomer as necessary.

[0070] As a styrene-based elastomer other than the amino group-containing styrene-based elastomer, a carboxyl group-containing styrene-based elastomer can be mentioned, for example.

[0071] The carboxyl group-containing styrene elastomer is effective as a component for imparting electrical properties in addition to adhesiveness and flexibility to a cured product.

[0072] By including the carboxyl group-containing styrene elastomer in the adhesive composition, the adhesion of the adhesive layer is improved. In addition, since the carboxyl group-containing styrene elastomer is reactive, the heat resistance and chemical resistance of the adhesive layer are also improved by epoxy curing.

[0073] The carboxyl group-containing styrene elastomer is a copolymer mainly composed of a block or random structure of a conjugated diene compound and an aromatic vinyl compound, and a hydrogenated product thereof modified with an unsaturated carboxylic acid.

[0074] The conjugated diene compound or the aromatic vinyl compound is as described in the above-mentioned column of <amino group-containing styrene elastomer>.

[0075] The modification of the carboxyl group-containing styrene elastomer can be performed, for example, by copolymerizing an unsaturated carboxylic acid during polymerization of the styrene elastomer, or by heating and kneading the styrene elastomer and the unsaturated carboxylic acid in the presence of an organic peroxide.

[0076] Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid, itaconic acid, fumaric acid, maleic anhydride, and itaconic anhydride.

[0077] The modification amount by the unsaturated carboxylic acid is preferably 0.1 to 10% by mass.

[0078] The acid value of the carboxyl-containing styrene elastomer is preferably 0.1 to 25 mgKOH / g, more preferably 0.5 to 23 mgKOH / g. When the acid value is 0.1 mgKOH / g or more, the adhesive composition is sufficiently cured to obtain good adhesion and heat resistance. On the other hand, when the acid value is 25 mgKOH / g or less, the adhesive strength and electrical properties are excellent.

[0079] In addition, the weight average molecular weight of the styrene elastomer containing a carboxyl group is preferably 1 to 500,000, more preferably 3 to 300,000, and further preferably 5 to 200,000. If the weight average molecular weight is above the above lower limit, excellent adhesion can be achieved, and the coating property when dissolved in a solvent and applied is also good. If the weight average molecular weight is below the above upper limit, the compatibility with the epoxy resin becomes good.

[0080] Specific examples of the carboxyl group-containing styrene-based elastomers include products obtained by modifying styrene-butadiene block copolymers, styrene-ethylene propylene block copolymers, styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, styrene-ethylene butylene-styrene block copolymers, and styrene-ethylene propylene-styrene block copolymers with unsaturated carboxylic acids.

[0081] These carboxyl group-containing styrene-based elastomers may be used alone or in combination of two or more.

[0082] Among the above copolymers, styrene-ethylene butylene-styrene block copolymers and styrene-ethylene propylene-styrene block copolymers are preferred from the viewpoints of adhesiveness and electrical properties.

[0083] In addition, the mass ratio of styrene / ethylene butylene in the styrene-ethylene butylene-styrene block copolymer and the mass ratio of styrene / ethylene propylene in the styrene-ethylene propylene-styrene block copolymer are preferably 10 / 90 to 50 / 50, and more preferably 20 / 80 to 40 / 60. If the mass ratio is within this range, an adhesive composition having excellent adhesive properties can be prepared.

[0084] <Other ingredients>

[0085] The adhesive composition may contain, in addition to the above-mentioned amino-containing styrene elastomer and epoxy resin, and, if necessary, a carboxyl-containing styrene elastomer, other thermoplastic resins, tackifiers, flame retardants, curing agents, curing accelerators, coupling agents, heat aging inhibitors, leveling agents, defoaming agents, inorganic fillers, pigments, and solvents other than these styrene elastomers to the extent that the functions of the adhesive composition are not affected.

[0086] Among the above-mentioned other components, as the above-mentioned other thermoplastic resins, for example, phenoxy resins, polyamide resins, polyester resins, polycarbonate resins, polyphenylene ether resins, polyurethane resins, polyacetal resins, polyethylene resins, polypropylene resins and polyethylene resins etc. can be mentioned. These thermoplastic resins can be used alone or in combination of two or more.

[0087] Examples of the tackifier include coumarone-indene resins, terpene resins, terpene-phenolic resins, rosin resins, p-tert-butylphenol-acetylene resins, phenol-formaldehyde resins, xylene-formaldehyde resins, petroleum hydrocarbon resins, hydrogenated hydrocarbon resins, turpentine resins, etc. These tackifiers may be used alone or in combination of two or more.

[0088] The flame retardant may be any of an organic flame retardant and an inorganic flame retardant. Examples of the organic flame retardant include melamine phosphate, melamine polyphosphate, guanidine phosphate, guanidine polyphosphate, ammonium phosphate, ammonium polyphosphate, ammonium amide phosphate, ammonium polyphosphate amide, phosphoric acid carbamate, polyphosphoric acid carbamate, aluminum tris(diethylphosphinate), aluminum tris(methylethylphosphinate), aluminum tris(diphenylphosphinate), zinc bis(diethylphosphinate), zinc bis(methylethylphosphinate), zinc bis(diphenylphosphinate), and zinc bis(diethylphosphinate). Phosphorus flame retardants such as titanium oxide, titanium tetrakis (diethylphosphinate), titanium bis (methylethylphosphinate), titanium tetrakis (methylethylphosphinate), titanium bis (diphenylphosphinate), titanium tetrakis (diphenylphosphinate); nitrogen flame retardants such as triazine compounds such as melamine, melam, melamine cyanurate, cyanuric acid compounds, isocyanuric acid compounds, triazole compounds, tetrazole compounds, diazo compounds, urea; silicon flame retardants such as organosilicon compounds and silane compounds. In addition, as inorganic flame retardants, metal hydroxides such as aluminum hydroxide, magnesium hydroxide, zirconium hydroxide, barium hydroxide, and calcium hydroxide can be cited; metal oxides such as tin oxide, aluminum oxide, magnesium oxide, zirconium oxide, zinc oxide, molybdenum oxide, and nickel oxide; zinc carbonate, magnesium carbonate, barium carbonate, zinc borate, hydrated glass, etc. These flame retardants can be used in combination of two or more.

[0089] As the above-mentioned curing agent, amine curing agents, acid anhydride curing agents, etc. can be cited, but it is not limited to these. As the amine curing agent, for example, melamine resins such as methylated melamine resins, butylated melamine resins, and benzoguanamine resins, dicyandiamide, 4,4'-diphenyldiaminosulfone, etc. can be cited. In addition, as acid anhydrides, aromatic acid anhydrides and aliphatic acid anhydrides can be cited. These curing agents can be used alone or in combination of two or more.

[0090] The content of the curing agent is preferably 0.05 to 100 parts by mass, more preferably 5 to 70 parts by mass, based on 100 parts by mass of the adhesive composition.

[0091] The curing accelerator is used to accelerate the reaction between the amino group-containing styrene elastomer and the epoxy resin, or between epoxy resins, and a tertiary amine curing accelerator, a tertiary amine salt curing accelerator, an imidazole curing accelerator, or the like can be used.

[0092] Examples of the tertiary amine curing accelerator include benzyldimethylamine, 2-(dimethylaminomethyl)phenol, 2,4,6-tris(dimethylaminomethyl)phenol, tetramethylguanidine, triethanolamine, N,N′-dimethylpiperazine, triethylenediamine, and 1,8-diazabicyclo[5.4.0]undecene.

[0093] Examples of the tertiary amine salt curing accelerator include 1,8-diazabicyclo[5.4.0]undecene, formate, octanoate, p-toluenesulfonate, phthalate, phenolate, or phenol novolac resin salts; and 1,5-diazabicyclo[4.3.0]nonene, formate, octanoate, p-toluenesulfonate, phthalate, phenolate, or phenol novolac resin salts.

[0094] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-methyl-4-ethylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 2,4-diamino-6-[2'-methylimidazolyl-(1')]ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]ethyl-s-triazine, -undecyl imidazolyl-(1')]ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, etc. These curing accelerators may be used alone or in combination of two or more.

[0095] When the adhesive composition contains a curing accelerator, the content of the curing accelerator is preferably 0.05 to 10 parts by mass, more preferably 0.1 to 5 parts by mass relative to 100 parts by mass of the adhesive composition. If the content of the curing accelerator is within the above range, the reaction between the amino group-containing styrene elastomer and the epoxy resin can be easily performed, and adhesion and heat resistance can be easily ensured.

[0096] In addition, examples of the coupling agent include silane coupling agents such as vinyl trimethoxysilane, 3-glycidoxypropyl trimethoxysilane, p-phenylvinyl trimethoxysilane, 3-methacryloxypropyl methyl dimethoxysilane, 3-acryloxypropyl trimethoxysilane, N-2-(aminoethyl)-3-aminopropyl methyl dimethoxysilane, 3-ureidopropyl triethoxysilane, 3-mercaptopropyl methyl dimethoxysilane, bis(triethoxysilylpropyl) tetrasulfide, 3-isocyanate propyl triethoxysilane, and imidazole silane; titanate coupling agents; aluminate coupling agents; zirconium coupling agents, etc. These may be used alone or in combination of two or more.

[0097] Examples of the heat aging inhibitor include phenolic antioxidants such as 2,6-di-tert-butyl-4-methylphenol, n-octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl) propionate, tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]methane, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenol, triethylene glycol-bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl) propionate; sulfur antioxidants such as dilauryl 3,3'-thiodipropionate and dimyristyl 3,3'-dithiopropionate; phosphorus antioxidants such as tris(nonylphenyl) phosphite and tris(2,4-di-tert-butylphenyl) phosphite. These may be used alone or in combination of two or more.

[0098] Examples of the inorganic filler include powders containing titanium oxide, aluminum oxide, zinc oxide, carbon black, silicon dioxide, talc, copper, silver, etc. These may be used alone or in combination of two or more.

[0099] (Adhesive layer)

[0100] The adhesive layer of the present invention contains the adhesive composition of the present invention described above.

[0101] The adhesive composition forming the adhesive layer can be cured.

[0102] The curing method is not particularly limited and can be appropriately selected depending on the intended purpose. For example, thermal curing may be used.

[0103] The thickness of the adhesive layer is not particularly limited and can be appropriately selected depending on the intended purpose. For example, it is preferably 3 to 100 μm, more preferably 5 to 70 μm, and further preferably 10 to 50 μm.

[0104] <Method for producing adhesive layer>

[0105] The adhesive layer can be produced by forming the adhesive composition into a film.

[0106] The adhesive composition can be manufactured by mixing amino-containing styrene elastomers, epoxy resins, and other elastomers (elastomers other than amino-containing styrene elastomers) or other components. The mixing method is not particularly limited as long as the adhesive composition is uniform. The adhesive composition is preferably used in the state of a solution or a dispersion, and therefore, usually, a solvent is also used.

[0107] Examples of the solvent include: alcohols such as methanol, ethanol, isopropanol, n-propanol, isobutanol, n-butanol, benzyl alcohol, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, and diacetone alcohol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl amyl ketone, cyclohexanone, and isophorone; aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and mesitylene; esters such as methyl acetate, ethyl acetate, ethylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; aliphatic hydrocarbons such as hexane, heptane, cyclohexane, and methylcyclohexane, etc. These solvents may be used alone or in combination of two or more.

[0108] When the adhesive composition is a solution or dispersion (resin varnish) containing a solvent, coating on a base film and formation of an adhesive layer can be smoothly performed, and an adhesive layer having a desired thickness can be easily obtained.

[0109] When the adhesive composition contains a solvent, the solid content concentration is preferably 3 to 80% by mass, more preferably 10 to 50% by mass, from the viewpoint of operability of forming the adhesive layer. When the solid content concentration is 80% by mass or less, the viscosity of the solution is appropriate and it is easy to apply evenly.

[0110] As a more specific embodiment of the method for producing the adhesive layer, after a resin varnish containing the above-mentioned adhesive composition and a solvent is applied to the surface of a substrate film to form a resin varnish layer, the solvent is removed from the resin varnish layer, thereby forming an adhesive layer in a B-stage state. Here, the adhesive layer being in a B-stage state means that the adhesive composition is in an uncured state or a semi-cured state in which a part of the adhesive composition begins to cure, and means a state in which the curing of the adhesive composition is further advanced by heating or the like.

[0111] Here, the method for coating the resin varnish on the substrate film is not particularly limited and can be appropriately selected according to the purpose. For example, it can include: spray coating, spin coating, dipping, roller coating, blade coating, doctor roll method, scraper coating, curtain coating, slit coating, screen printing, inkjet method, dispensing method, etc.

[0112] The adhesive layer in the B-stage state can be further heated or the like to form a cured adhesive layer.

[0113] <Adhesive layer characteristics>

[0114] In the adhesive layer formed of the adhesive composition of the present invention, the adhesive strength (adhesive strength, also referred to as peel strength in the present invention) (N / cm) between an adherend and a substrate film after curing is excellent.

[0115] As shown in the following examples, for example, when the peeling force (N / cm) was measured in a post-curing step at 150° C. after a lamination step at 120° C., an excellent result was obtained.

[0116] It should be noted that the lamination step herein refers to a heating step in which the heating time is short for temporarily fixing the adhesive layer to the adherend.

[0117] Furthermore, the adhesive layer comprising the adhesive composition of the present invention exhibits excellent adhesion (both referred to as adhesive force or peeling force) even during curing at a lower temperature.

[0118] As shown in the following examples, for example, after a lamination process at 120°C, when the peel force (N / cm) in a post-curing process at 120°C is measured, an excellent peel force is exhibited, which is close to the peel force (N / cm) in a post-curing process at 150°C.

[0119] [Peel force (N / cm)]

[0120] As for the peeling strength, the adhesive laminate cured at 120°C or 150°C was cut into test pieces with a width of 25 mm, and the peeling strength was measured when the electrolytic copper foil was peeled off from the base film with adhesive fixed to the support body at a peeling speed of 0.3 m / min and a peeling angle of 180° according to JIS Z0237:2009 (Testing method for adhesive tapes and adhesive sheets).

[0121] The adhesive layer of the present invention obtained by curing the adhesive composition preferably has a relative dielectric constant (εr) of 3.5 or less and a dielectric loss tangent (tan δ) of 0.01 or less as measured at a frequency of 28 GHz.

[0122] If the relative dielectric constant is 3.5 or less and the dielectric loss tangent is 0.01 or less, it can be suitably used even in FPC-related products that have strict requirements on electrical characteristics.

[0123] [Relative dielectric constant and dielectric loss tangent]

[0124] The relative dielectric constant and dielectric loss tangent of the adhesive layer can be measured by an open resonator method at a temperature of 23° C. and a frequency of 28 GHz using a network analyzer MS46122B (manufactured by Anritsu Corporation) and an open resonator Fabry-Perot DPS-03 (manufactured by KEYCOM Corporation).

[0125] (Laminated body)

[0126] The laminated body of the present invention comprises a base film and the above-mentioned adhesive layer disposed on at least one surface of the base film.

[0127] <Base film>

[0128] The substrate film used in the present invention can be selected according to the purpose of the laminate. For example, when the laminate is used as a cover film or a copper-clad laminate (CCL), polyimide film, polyetheretherketone film, polyphenylene sulfide film, aromatic polyamide film, polyethylene naphthalate film, and liquid crystal polymer film can be cited. Among these films, polyimide film, polyetheretherketone (PEEK) film, polyethylene naphthalate film, and liquid crystal polymer film are preferred from the viewpoint of adhesion and electrical properties.

[0129] In addition, when using the laminate of the present invention as an adhesive sheet, the base film needs to be a releasable film, for example, polyethylene terephthalate film, polyethylene film, polypropylene film, silicone release-treated paper, polyolefin resin coated paper, TPX (polymethylpentene) film, and fluorine-based resin film.

[0130] When the laminate of the present invention is used as a shielding film, the base film needs to be a film having an electromagnetic wave shielding capability, and examples thereof include a laminate of a protective insulating layer and a metal foil.

[0131] (covering film)

[0132] A cover film is mentioned as a preferable embodiment of the laminated body of the present invention.

[0133] When manufacturing an FPC, a laminate having an adhesive layer called a “cover film” is generally used to protect a wiring portion. The cover film includes an insulating resin layer and an adhesive layer formed on the surface thereof.

[0134] For example, the cover film is a laminated body in which the adhesive layer is formed on at least one surface of the base film, and the base film and the adhesive layer are generally difficult to peel off.

[0135] The thickness of the base film contained in the cover film is preferably 5 to 100 μm, more preferably 5 to 50 μm, and further preferably 5 to 30 μm. If the thickness of the base film is below the upper limit, the cover film can be thinned. If the thickness of the base film is above the lower limit, the design of the printed wiring board can be facilitated and the handling property is also good.

[0136] As a method for producing a covering film, for example, a resin varnish containing the above-mentioned adhesive composition and a solvent is applied to the surface of the above-mentioned base film to form a resin varnish layer, and then the solvent is removed from the resin varnish layer, thereby producing a covering film having a B-stage adhesive layer.

[0137] The drying temperature when removing the solvent is preferably 40 to 250°C, more preferably 70 to 170°C.

[0138] Drying is performed by passing the laminated body coated with the adhesive composition through an oven that performs hot air drying, far infrared heating, high-frequency induction heating, or the like.

[0139] It should be noted that, as required, a release film may be laminated on the surface of the adhesive layer for storage, etc. As the release film, known films such as polyethylene terephthalate film, polyethylene film, polypropylene film, silicone release treated paper, polyolefin resin coated paper, TPX film, and fluorine resin film may be used.

[0140] Since the cover film of the present invention uses the low-dielectric adhesive composition of the present invention, high-speed transportation of electronic devices is possible and the cover film of the present invention also has excellent adhesion stability to the electronic devices.

[0141] (Adhesive sheet)

[0142] As a preferred embodiment of the laminated body of the present invention, an adhesive sheet can be mentioned.

[0143] The bonding sheet is formed with the above-mentioned adhesive layer on the surface of the release film (base film). In addition, the bonding sheet can also be a mode in which the adhesive layer is provided between two release films. When using the bonding sheet, the release film is peeled off and used. The release film can use the same film as the film recorded in the column of the above-mentioned (cover film).

[0144] The thickness of the base film included in the adhesive sheet is preferably 5 to 100 μm, more preferably 25 to 75 μm, and further preferably 38 to 50 μm. When the thickness of the base film is within the above range, the adhesive sheet can be easily manufactured and has good handling properties.

[0145] As a method for producing an adhesive sheet, for example, there is a method in which a resin varnish containing the above-mentioned adhesive composition and a solvent is applied on the surface of a release film and dried in the same manner as in the case of the above-mentioned cover film.

[0146] The adhesive sheet of the present invention uses the low-dielectric adhesive composition of the present invention, and therefore can carry out high-speed transportation of electronic devices, and also has excellent adhesion stability with electronic devices.

[0147] (Copper Clad Laminate (CCL))

[0148] As a preferred embodiment of the laminate of the present invention, there is mentioned a copper-clad laminate in which a copper foil is bonded to the adhesive layer in the laminate of the present invention.

[0149] The copper-clad laminate is formed by using the above-mentioned laminate and laminating copper foil, for example, in the order of a base film, an adhesive layer, and copper foil. The adhesive layer and copper foil may be formed on both sides of the base film.

[0150] The adhesive composition used in the present invention is also excellent in adhesion to articles containing copper.

[0151] The copper-clad laminate of the present invention uses the low-dielectric adhesive composition of the present invention, and therefore can perform high-speed transmission of electronic devices and has excellent adhesive stability.

[0152] As a method for manufacturing a copper-clad laminate, there is, for example, a method in which the adhesive layer and the copper foil of the laminate are brought into surface contact, heat-laminated at 80° C. to 150° C., and the adhesive layer is further cured by post-curing. The post-curing conditions are, for example, 100° C. to 200° C. and 30 minutes to 4 hours in an atmosphere of an inert gas. It should be noted that the copper foil is not particularly limited, and electrolytic copper foil, rolled copper foil, etc. can be used.

[0153] (Printed Circuit Board)

[0154] As a preferred embodiment of the laminate of the present invention, there is mentioned a printed wiring board in which copper wiring is bonded to the adhesive layer in the laminate of the present invention.

[0155] The printed wiring board is obtained by forming an electronic circuit on the above copper-clad laminate.

[0156] The printed wiring board is formed by laminating a base film and copper wiring using the above-mentioned laminate, and the base film, the adhesive layer and the copper wiring are formed in this order. It should be noted that the adhesive layer and the copper wiring may be formed on both sides of the base film.

[0157] For example, a cover film is attached to the surface having the wiring portion via an adhesive layer by heat pressing or the like, thereby manufacturing a printed wiring board.

[0158] The printed wiring board of the present invention uses the low-dielectric adhesive composition of the present invention, and therefore can perform high-speed transmission of electronic equipment and has excellent adhesive stability.

[0159] As a method for manufacturing the printed wiring board of the present invention, there is, for example, a method in which the adhesive layer of the laminate is brought into contact with the copper wiring, heat-laminated at 80° C. to 150° C., and the adhesive layer is cured by post-curing. The post-curing conditions can be set to, for example, 100° C. to 200° C. for 30 minutes to 4 hours. The shape of the copper wiring is not particularly limited, and an appropriate shape can be selected as desired.

[0160] (Shielding Film)

[0161] As a preferred embodiment of the laminated body of the present invention, a barrier film can be mentioned.

[0162] Shielding films are used to shield various electronic devices in order to block electromagnetic noise that may affect computers, mobile phones, analytical equipment, and other electronic devices and cause malfunctions. They are also called electromagnetic wave shielding films.

[0163] The electromagnetic wave shielding film is formed by laminating, for example, an insulating resin layer, a metal layer, and the adhesive layer of the present invention in this order.

[0164] The shielding film of the present invention uses the low-dielectric adhesive composition of the present invention, and therefore can perform high-speed transmission of electronic devices, and also has excellent adhesion stability with electronic devices.

[0165] (Printed circuit board with shielding film)

[0166] As a preferred embodiment of the laminated body of the present invention, a printed wiring board with a shielding film can be mentioned.

[0167] The printed wiring board with a shielding film is a printed wiring board in which the above-mentioned electromagnetic wave shielding film is attached to a printed wiring board having a printed circuit provided on at least one surface of a substrate.

[0168] The printed wiring board with a shielding film includes, for example, a printed wiring board, an insulating film adjacent to a surface of the printed wiring board on which a printed circuit is provided, and the electromagnetic wave shielding film described above.

[0169] The printed wiring board with a shielding film of the present invention uses the adhesive composition of the present invention having a low dielectric constant, and therefore can perform high-speed transmission of electronic equipment and has excellent adhesion stability.

[0170] Example

[0171] The present invention will be described in more detail below with reference to Examples, but the scope of the present invention is not limited to these Examples. It should be noted that, in the following description, parts and % are by mass unless otherwise specified.

[0172] (Amino group-containing styrene elastomer)

[0173] The product name "Tuftec MP10" (amine-modified styrene-ethylene butylene-styrene copolymer) manufactured by Asahi Kasei Corporation was used. The styrene / ethylene butylene ratio of the copolymer was 30 / 70, and the weight average molecular weight was 78,000. The total nitrogen content of the copolymer was 426 ppm.

[0174] (Amino group-containing styrene elastomer)

[0175] The product name "Tuftec MPLH-01" (amine-modified styrene-ethylene butylene-styrene copolymer) manufactured by Asahi Kasei Corporation was used. The styrene / ethylene butylene ratio of the copolymer was 20 / 80, and the weight average molecular weight was 100,000. The total nitrogen content of the copolymer was 432 ppm.

[0176] (Amino group-containing styrene elastomer)

[0177] The product name "Tuftec MPHF-02" (amine-modified styrene-ethylene butylene-styrene copolymer) manufactured by Asahi Kasei Corporation was used. The styrene / ethylene butylene ratio of the copolymer was 30 / 70, and the weight average molecular weight was 68,000. The total nitrogen content of the copolymer was 496 ppm.

[0178] (Carboxyl group-containing styrene elastomer)

[0179] The product name "Tuftec M1911" (maleic acid-modified styrene-ethylene butylene-styrene block copolymer) manufactured by Asahi Kasei Corporation was used. The copolymer had an acid value of 2 mgKOH / g, a styrene / ethylene butylene ratio of 30 / 70, and a weight average molecular weight of 69,000.

[0180] (Carboxyl group-containing styrene elastomer)

[0181] The product name "Tuftec M1913" (maleic acid-modified styrene-ethylene butylene-styrene block copolymer) manufactured by Asahi Kasei Corporation was used. The copolymer had an acid value of 10 mgKOH / g, a styrene / ethylene butylene ratio of 30 / 70, and a weight average molecular weight of 67,000.

[0182] (Styrene elastomer)

[0183] Kraton G1651 (styrene-ethylene butylene-styrene block copolymer) manufactured by Kraton Co. was used. The copolymer had an acid value of 0 mgKOH / g, a styrene / ethylene butylene ratio of 33 / 67, and a weight average molecular weight of 136,700.

[0184] (Epoxy resin)

[0185] As the epoxy resin, a novolac-type epoxy resin, trade name "YX7700" (softening point 65° C.), manufactured by Mitsubishi Chemical Corporation, was used.

[0186] (Epoxy resin)

[0187] As the epoxy resin, a glycidylamine-based epoxy resin, trade name "jER604" (liquid epoxy) manufactured by Mitsubishi Chemical Corporation, was used.

[0188] (Epoxy resin)

[0189] As the epoxy resin, trade name "jER1031S" (softening point 92° C.) manufactured by Mitsubishi Chemical Corporation was used.

[0190] (Epoxy resin)

[0191] The product name "Epofriend CT310" (epoxide of styrene-butadiene block copolymer) manufactured by DAICEL was used. The copolymer had a styrene / ethylene butene ratio of 40 / 60, a weight average molecular weight of 93,000, and an epoxy equivalent of 2125 g / eq.

[0192] (Solvent)

[0193] A mixed solvent consisting of toluene and methyl ethyl ketone (mass ratio = 90:10) was used.

[0194] (Base film)

[0195] As the base film, "Shin-Etsu Sepla Film PEEK" (polyetheretherketone, thickness 50 μm) manufactured by Shin-Etsu Polymer Co., Ltd. was used.

[0196] (Electrolytic Copper Foil)

[0197] As the electrolytic copper foil, "TQ-M7-VSP" manufactured by Mitsui Mining & Smelting Co., Ltd. (electrolytic copper foil, thickness 12 μm, glossy surface Rz 1.27 μm, glossy surface Ra 0.197 μm, glossy surface Rsm 12.95 μm) was used. The surface roughness of the glossy surface is a value obtained by measuring a roughness curve using a laser microscope and based on the roughness curve in accordance with JIS B 0601: 2013 (ISO 4287: 1997 Amd. 1: 2009).

[0198] (Release film)

[0199] As a release film, NP75SA (silicone release PET film, 50 μm) manufactured by PANAC Corporation was used.

[0200] (Determination of nitrogen content)

[0201] The total nitrogen content contained in the amino group-containing styrene-based elastomer used in Examples was determined by the following method.

[0202] <Measurement method>

[0203] It was determined in accordance with JIS-K2609 using a trace nitrogen analyzer ND-100 (manufactured by Mitsubishi Chemical Corporation).

[0204] (Example 1)

[0205] <150℃ Curing Process>

[0206] The components constituting the adhesive layer shown in Table 1 were contained in the proportions shown in Table 1, and these components were dissolved in a solvent to prepare a resin varnish having a solid content concentration of 20% by mass.

[0207] The surface of the base film is subjected to corona treatment.

[0208] The resin varnish was applied to the surface of the substrate film and dried in an oven at 110° C. for 4 minutes to volatilize toluene, thereby forming an adhesive layer to obtain a substrate film with an adhesive. The adhesive layer of the adhesive laminate was overlapped with the shiny surface of the electrolytic copper foil in contact with each other, and heat-laminated at 120° C. to obtain a pre-cured adhesive laminate. The pre-cured adhesive laminate was further post-cured at 150° C. for 60 minutes to cure the adhesive layer and obtain a post-cured adhesive laminate.

[0209] The peeling force (N / cm) between the electrolytic copper foil and the base film of the adhesive laminated body after curing at 150° C. of Example 1 was measured.

[0210] <120℃ Curing Process>

[0211] Using the same adhesive composition as in the above-mentioned <150° C. curing step> (containing the components constituting the adhesive layer shown in Table 1 at the ratios shown in Table 1), these components were dissolved in a solvent to prepare a resin varnish.

[0212] The resin varnish was applied to the surface of the substrate film and dried in an oven at 110° C. for 4 minutes to volatilize toluene, thereby forming an adhesive layer to obtain a substrate film with an adhesive. The adhesive layer of the adhesive laminate was overlapped with the shiny surface of the electrolytic copper foil in contact with each other, and heat-laminated at 120° C. to obtain a pre-cured adhesive laminate. The pre-cured adhesive laminate was further post-cured at 120° C. for 30 minutes to cure the adhesive layer and obtain a post-cured adhesive laminate.

[0213] The peeling force (N / cm) between the electrolytic copper foil and the base film of the adhesive laminated body after curing at 120° C. of Example 1 was measured.

[0214] [Peel force (N / cm)]

[0215] As for the peeling strength, the adhesive laminate cured at 120°C or 150°C was cut into test pieces with a width of 25 mm, and the peeling strength of the electrolytic copper foil was measured by peeling it off from the base film with adhesive fixed to the support at a peeling speed of 0.3 m / min and a peeling angle of 180° according to JIS Z0237:2009 (Testing method for adhesive tapes and adhesive sheets).

[0216] Furthermore, the relative dielectric constant and dielectric loss tangent of the adhesive layer in the laminate of Example 1 at a frequency of 28 GHz were also measured.

[0217] [Relative dielectric constant and dielectric loss tangent]

[0218] As for the relative dielectric constant and dielectric loss tangent of the adhesive layer, the network analyzer MS46122B (manufactured by Anritsu) and the open resonator Fabry-Perot DPS-03 (manufactured by KEYCOM) were used to measure the temperature at 23°C and the frequency at 28GHz by the open resonator method. As for the measured sample, the resin varnish was roller-coated on the release film, and then the film with the coating was placed in an oven and dried at 110°C for 4 minutes to form an adhesive layer (thickness 50μm) in a Class B state. Then, the adhesive layer was thermally laminated at 120°C in a manner where the bonding surfaces were in contact with each other to form an adhesive film (thickness 100μm) before curing. The adhesive film (thickness 100μm) before curing was placed in an oven and heated and cured at 150°C for 60 minutes to prepare a cured adhesive film (100mm×100mm). The release film was peeled off from the cured adhesive film, and the relative dielectric constant and dielectric loss tangent of the adhesive layer were measured.

[0219] [Acid resistance]

[0220] The cured adhesive laminate of Example 1 was cut into test pieces of 30×30 mm and immersed in a 10% sulfuric acid aqueous solution for 3 hours to conduct an acid resistance test.

[0221] The acid resistance of the copper-clad laminate (CCL) having the adhesive layer of the present invention was evaluated according to the following evaluation criteria.

[0222] A No peeling occurred. Very good acid resistance.

[0223] B Some peeling was observed at the corners. Acid resistance was good.

[0224] C also peels off at the edge. Poor acid resistance.

[0225] [Alkali resistance]

[0226] The cured adhesive laminate of Example 1 was cut into test pieces of 30×30 mm and immersed in a 10% sodium hydroxide aqueous solution for 3 hours to conduct an alkali resistance test.

[0227] The alkali resistance of the copper-clad laminate (CCL) having the adhesive layer of the present invention was evaluated according to the following evaluation criteria.

[0228] A No peeling occurred. Very good alkali resistance.

[0229] B Some peeling is observed at the corners. Alkali resistance is good.

[0230] C also has peeling on the edge. Poor alkali resistance.

[0231] Table 1 shows the measurement results.

[0232] (Example 2 to Example 10)

[0233] Except that the types and blending amounts of the components constituting the adhesive layer in Example 1 were changed as shown in Table 1, the same procedure as in Example 1 was carried out to produce laminated bodies of Examples 2 to 10.

[0234] The same evaluation as in Example 1 was performed on the produced laminate.

[0235] Table 1 shows the results.

[0236] (Comparative Example 1 to Comparative Example 4)

[0237] Laminated bodies of Comparative Examples 1 to 4 were prepared in the same manner as in Example 1 except that the types and blending amounts of the components constituting the adhesive layer in Example 1 were changed as shown in Table 1.

[0238] The same evaluation as in Example 1 was performed on the produced laminate.

[0239] Table 1 shows the results.

[0240] [Table 1]

[0241]

[0242] As shown in Examples 1 to 10, it was confirmed that the adhesive layer including the adhesive composition of the present invention exhibited excellent adhesion (tackiness) after being cured by heating at 150°C.

[0243] Furthermore, it was confirmed that the adhesive layer comprising the adhesive composition of the present invention exhibited a peeling force substantially the same as the peeling force at 150° C. after heat curing at a lower temperature of 120° C., and exhibited excellent adhesion (adhesive force).

[0244] This application claims priority based on Japanese Patent Application No. 2019-231643, filed on December 23, 2019, and cites all the contents described in the Japanese Patent Application.

[0245] Industrial Applicability

[0246] The laminate having an adhesive layer containing the adhesive composition of the present invention can be suitably used in the production of FPC-related products for electronic devices such as smartphones, mobile phones, optical modules, digital cameras, game consoles, notebook computers, and medical devices.

Claims

1. An adhesive layer in a B-stage state, which is formed from an adhesive composition, The adhesive composition comprises a styrene elastomer containing an amino group and an epoxy resin. The epoxy resin is a novolac epoxy resin, a glycidylamine epoxy resin, or an epoxy compound of a styrene-butadiene block copolymer. The total nitrogen content of the amino group-containing styrene elastomer is 50 to 5000 ppm, The content of the amino group-containing styrene-based elastomer is 25.0 to 99.0 parts by mass based on 100 parts by mass of the solid content of the adhesive composition. The content of the epoxy resin is 1 to 20 parts by mass relative to 100 parts by mass of the solid content of the adhesive composition. The relative dielectric constant of the cured adhesive layer obtained by curing the adhesive layer in the B-stage state measured at a frequency of 28 GHz is 3.5 or less, and the dielectric loss tangent is 0.01 or less.

2. The adhesive layer according to claim 1, wherein The softening point or melting point of the epoxy resin is below 90°C.

3. A laminate comprising: a substrate film; and The adhesive layer according to claim 1 or 2.

4. The laminate according to claim 3, wherein: The substrate film contains polyetheretherketone (PEEK) resin.

5. A cover film with an adhesive layer, comprising a laminate, The laminated body has: a substrate film; and The adhesive layer according to claim 1 or 2.

6. A copper-clad laminate comprising a laminate having a base film and an adhesive layer, The adhesive layer comprises an adhesive composition, The adhesive composition comprises an amino group-containing styrene-based elastomer and an epoxy resin, wherein the epoxy resin is a novolac-type epoxy resin, a glycidylamine-type epoxy resin, or an epoxy compound of a styrene-butadiene block copolymer, the amino group-containing styrene-based elastomer has a weight average molecular weight of 10,000 to 500,000 and a total nitrogen content of 50 to 5,000 ppm, the content of the amino group-containing styrene-based elastomer is 25.0 to 99.0 parts by mass relative to 100 parts by mass of the solid content of the adhesive composition, and the content of the epoxy resin is 1 to 20 parts by mass relative to 100 parts by mass of the solid content of the adhesive composition.

7. A printed wiring board comprising a laminate having a base film and an adhesive layer, The adhesive layer comprises an adhesive composition, The adhesive composition comprises an amino group-containing styrene-based elastomer and an epoxy resin, wherein the epoxy resin is a novolac-type epoxy resin, a glycidylamine-type epoxy resin, or an epoxy compound of a styrene-butadiene block copolymer, the amino group-containing styrene-based elastomer has a weight average molecular weight of 10,000 to 500,000 and a total nitrogen content of 50 to 5,000 ppm, the content of the amino group-containing styrene-based elastomer is 25.0 to 99.0 parts by mass relative to 100 parts by mass of the solid content of the adhesive composition, and the content of the epoxy resin is 1 to 20 parts by mass relative to 100 parts by mass of the solid content of the adhesive composition.

8. A shielding film comprising a laminate having a base film and an adhesive layer, The adhesive layer comprises an adhesive composition, The adhesive composition comprises an amino group-containing styrene-based elastomer and an epoxy resin, wherein the epoxy resin is a novolac-type epoxy resin, a glycidylamine-type epoxy resin, or an epoxy compound of a styrene-butadiene block copolymer, the amino group-containing styrene-based elastomer has a weight average molecular weight of 10,000 to 500,000 and a total nitrogen content of 50 to 5,000 ppm, the content of the amino group-containing styrene-based elastomer is 25.0 to 99.0 parts by mass relative to 100 parts by mass of the solid content of the adhesive composition, and the content of the epoxy resin is 1 to 20 parts by mass relative to 100 parts by mass of the solid content of the adhesive composition.

9. A printed wiring board with a shielding film, comprising a laminate having a base film and an adhesive layer, The adhesive layer comprises an adhesive composition, The adhesive composition comprises an amino group-containing styrene-based elastomer and an epoxy resin, wherein the epoxy resin is a novolac-type epoxy resin, a glycidylamine-type epoxy resin, or an epoxy compound of a styrene-butadiene block copolymer, the amino group-containing styrene-based elastomer has a weight average molecular weight of 10,000 to 500,000 and a total nitrogen content of 50 to 5,000 ppm, the content of the amino group-containing styrene-based elastomer is 25.0 to 99.0 parts by mass relative to 100 parts by mass of the solid content of the adhesive composition, and the content of the epoxy resin is 1 to 20 parts by mass relative to 100 parts by mass of the solid content of the adhesive composition.